The Informatization Construction and Use of Primary Health Institutions in Jiangsu Province - Chunguo XING, Yingqiu XIA, Danyun WU, Yunxia LIAO, Ning ZHAO (Zhongguo quanke yixue, 2022)
Background During the 13th Five-Year Plan in China, the rapid development of the informatization construction in the primary health of China has greatly promoted the improvement of the service level and quality of the primary health institutions, but there are still deficiencies in some aspects. Objective To investigate the status of informatization construction of primary health institutions in Jiangsu Province, in order to analyze the existing problems and provide corresponding countermeasures. Methods From July to October 2020, a stratified random sampling method was used to select 500 primary health institutions from 13 cities in Jiangsu Province to carry out a questionnaire survey. The contents of the questionnaire included the financial planning and fund sources for infomatization construction of the primary health institutions, status of information system construction of hospitals, the informatization of residents' health records, the deployment of informatization staffs, medical information sharing, status of telemedicine and satisfaction to the informationization of the primary health institutions. The vice president of business filled in the questionnaire according to the truth. Results A total of 416 valid questionnaires from the primary health institutions were obtained, accounting for 26.5% (416/1 567) of all the primary health institutions in the province. 80.0% (333/416) of the informatization construction of primary health institutions is planned by the county (city, district) government, and 67.3% (280/416) got fund from the government finance. 99.0% (412/416) of the primary health institutions constructed hospital information management system, 92.1% (383/416) constructed outpatient system, 81.7% (340/416) constructed electronic medical record system, 45.0% (187/416) constructed clinical information system, 98.3% (409/416) constructed information system of residents' health records. 31.3% (130/416) of the primary health institutions shared medical information to the patients, 83.9% (349/416) shared the medical information to the community health service station and the village clinics, 14.2% (59/416) shared the medical information to the superior hospitals, 29.1% (121/416) shared the medical information over the county, 4.3% (18/416) shared the medical information over the city. 38.2% (159/416) of the primary health institutions carried out such services as online appointment, ECG or CT diagnosis, and 15.6% (65/416) carried out real-time outpatient service. 81.3% (338/416) of the primary health institutions showed satisfaction to the informatization construction, and the institutions with different types or in different cities showed different satisfaction. Conclusion The overall informatization of primary health institutions in Jiangsu is is relatively good, but there are still phenomena such as unbalanced regional development, low level of cross-regional information sharing and lack of popularization of telemedicine, which needs to be further improved.